Ribosomal readthrough at a short UGA stop codon context triggers dual localization of metabolic enzymes in Fungi and animals. - Alina C Stiebler; Johannes Freitag; Kay O Schink; Thorsten Stehlik; Britta A M Tillmann; Julia Ast; Michael Bölker (PLoS Genetics, 2014)
Translation of mRNA into a polypeptide chain is a highly accurate process. Many prokaryotic and eukaryotic viruses, however, use leaky termination of translation to optimize their coding capacity. Although growing evidence indicates the occurrence of ribosomal readthrough also in higher organisms, a biological function for the resulting extended proteins has been elucidated only in very few cases. Here, we report that in human cells programmed stop codon readthrough is used to generate peroxisomal isoforms of cytosolic enzymes. We could show for NAD-dependent lactate dehydrogenase B (LDHB) and NAD-dependent malate dehydrogenase 1 (MDH1) that translational readthrough results in C-terminally extended protein variants containing a peroxisomal targeting signal 1 (PTS1). Efficient readthrough occurs at a short sequence motif consisting of a UGA termination codon followed by the dinucleotide CU. Leaky termination at this stop codon context was observed in fungi and mammals. Comparative genome analysis allowed us to identify further readthrough-derived peroxisomal isoforms of metabolic enzymes in diverse model organisms. Overall, our study highlights that a defined stop codon context can trigger efficient ribosomal readthrough to generate dually targeted protein isoforms. We speculate that beyond peroxisomal targeting stop codon readthrough may have also other important biological functions, which remain to be elucidated.